Pengaruh Store Atmosphere, Brand Image Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Di Cafe Kopinan.Id Karanganyar: Studi Kasus Kepuasan konsumen Di Cafe Kopinan.id Karanganyar - Septiyana Tri Handayani; Titin Hargyatni (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine and analyze the direct effect of store atmosphere on consumer satisfaction at Kafe Kopinan.id Karanganyar Consumers, to determine and analyze the direct effect of brand image on consumer satisfaction at Kafe Kopinan.id Karanganyar Consumers, to determine and analyze the direct effect of service quality on consumer satisfaction at Kafe Kopinan.id Karanganyar Consumers and to determine and analyze the simultaneous effect of store atmosphere, brand image, service quality on consumer satisfaction at Kafe Kopinan.id Karanganyar Consumers. This study uses a quantitative method with a sample of 100 employee respondents at Kafe Kopinan.id Karanganyar Consumers. Data were analyzed using multiple linear regression analysis tests using IBM SPSS Statistics. The results of the study indicate that directly store atmosphere has a significant effect on consumer satisfaction at Cafe Kopinan.id Karanganyar Consumers, directly service quality has a significant effect on consumer satisfaction at Cafe Kopinan.id Karanganyar Consumers, directly brand image has a significant effect on consumer satisfaction at Cafe Kopinan.id Karanganyar Consumers, and directly and simultaneously store atmosphere, brand image, and service quality have a significant effect on consumer satisfaction at Cafe Kopinan.id Karanganyar Consumers.